Assessing the impact of one belt and road (OBOR) initiative on trade potential and transportation efficiency using a gravity model analysis - Alshreef Abed; Kazeem Babatunde; Aza Azlina; Osman Ghanem; Saidat O. Onikosi-Alliyu (Discover Sustainability)
Abstract Using a gravity model approach, this study evaluates the trade potential between China and its partner countries under the One Belt One Road (OBOR) initiative. By comparing actual trade flows with simulated scenarios based on improved infrastructure and economic integration, the analysis identifies countries and regions with the highest capacity for trade expansion. The results show that GDP size, trade openness, geographic distance, and transport infrastructure significantly influence bilateral trade flows. Countries with enhanced connectivity, particularly those situated along key OBOR corridors, are projected to benefit the most in relative and absolute terms. Beyond its economic implications, this research holds substantial value for sustainable development. It highlights how strategic infrastructure investment and trade facilitation can contribute to inclusive and sustainable growth. The study supports evidence-based policymaking that fosters regional integration, reduces trade-related inequalities, and promotes resilient, interconnected economies by identifying disparities and potential gains across regions.